2015
DOI: 10.1007/s13193-015-0456-2
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of External Breast Prosthesis Use by Post Mastectomy Breast Cancer Patients in India: Descriptive Study from Tertiary Care Centre

Abstract: In India, Breast cancer is now the most common cancer in urban and 2nd most common in rural areas [1]. The incidence is rising, more younger women are getting affected and due to increase in survival rates there is an increase in the total number of women suffering from breast Cancer. So far there are no studies evaluating the pattern of breast prosthesis use in Indian scenario. The aim of this study is to address the patterns of external breast prosthesis used in India and view of Indian women on such prosthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…In their study of investigating pattern of using EBP in India, Ramu et al . [ 26 ] found that high education level, young age, and living in city contribute to higher utilization of EBP. The researchers also reported that most of the EBP users wanted to improve the quality of EBP, including comfort, size, and shape as well as reduce the cost of EBP.…”
Section: Introductionmentioning
confidence: 99%
“…In their study of investigating pattern of using EBP in India, Ramu et al . [ 26 ] found that high education level, young age, and living in city contribute to higher utilization of EBP. The researchers also reported that most of the EBP users wanted to improve the quality of EBP, including comfort, size, and shape as well as reduce the cost of EBP.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the costs of cosmetic breast reconstruction surgery were prohibitively unaffordable to them. Therefore, a more affordable alternative is an external breast prosthesis, an artificial breast-shape material that is inserted into the bra to replace the lost breast [ 32 ]. External breast prostheses can be a viable option for some patients, but they do have some limitations; for instance, they may not provide the same level of comfort or natural appearance when compared to cosmetic breast reconstruction [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a more affordable alternative is an external breast prosthesis, an artificial breast-shape material that is inserted into the bra to replace the lost breast [ 32 ]. External breast prostheses can be a viable option for some patients, but they do have some limitations; for instance, they may not provide the same level of comfort or natural appearance when compared to cosmetic breast reconstruction [ 32 ]. They may require regular adjustments or replacements over time or cause discomfort or skin irritation from wearing them [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the education level an individual has, the wider the scope of their knowledge and the more multiple access they have to relevant knowledge. Studies on external breast prostheses in other countries have been more in-depth and detailed than those previously conducted in China (23)(24)(25)(26)(27). Thijs-Boer et al (28) examined patients undergoing radical mastectomies in the Netherlands and found that modern women were concerned with the convenience of wearing breast prostheses, local skin stimulation, the protection of the wound surface and the degree to which the breast prostheses fit to their bodies.…”
Section: Factors Affecting Medical Professionals' Knowledge Of the Us...mentioning
confidence: 99%